On the use of Simple Moving Averages for supply chains where information is not shared. Issue 3 (2015) - Ali, M.M.; Babai, M.Z.; Boylan, J.E.; Syntetos, A.A.
Abstract: Despite the evidence of benefits of information sharing, there are many supply chains that are unable to share information due to constraints such as compatibility of information systems, information quality, trust and confidentiality. Furthermore, a steady stream of papers has explored a phenomenon known as Downstream Demand Inference (DDI) where the upstream member in the supply chain can infer the downstream demand without the need of a formal information sharing mechanism. Recent research has shown that under a more practical setting, with less restrictive assumptions, DDI is not possible with optimal forecasting methods or Single Exponential Smoothing but is possible when supply chains use a Simple Moving Average (SMA) method. In this paper, we propose a simple DDI strategy based on SMA for supply chains where information cannot be shared. This strategy allows the upstream member in the supply chain to infer the consumer demand mathematically rather than sharing this. We compare the DDI strategy with the existing No Information Sharing (NIS) strategy. The comparison is made analytically which enables to show that using the DDI strategy reduces the MSE in the supply chains.